Use of Contextual Teaching and Learning (CTL) Assisted With Number Card Media in Understanding Numbers 1-10 in Children With Special Needs Class IV SDN Cibungkul - Meiliana Nurfitriani; Yopa Taufik Saleh; Melsa Rahayu Melsa (LPPM Universitas Buana Perjungan Karawang, 2021)
Based on the results of observations in grade IV SDN Cibungkul, it shows that in the learning process the teacher has not used the right learning method so that learning is less interesting and students think mathematics is a difficult subject. Students have difficulty solving problems and are less active in the learning process in class. The results of observations by researchers there were obstacles that were encountered at PLP 2 at SDN Cibungkul, namely the lack of students to be able to understand in recognizing numbers and children who were used as subjects, namely children with special needs (ABK) in grade IV. I made observations after PLP 2 by conducting interviews and testing the children with special needs. Based on this, the researcher wants to try to use the Contextual Teaching And Learning (CTL) approach assisted by number card media in understanding numbers 1-10 in children with special needs (ABK) in Class IV SDN Cibungkul. This study uses the case method with the subject of 1 student with special needs. Data analysis in qualitative research. The findings show that the use of number card media in understanding numbers 1-10 in children with special needs has gone well through various stages using the Contextual Teaching And Learning (CTL) learning method. Contextual methods assisted by number card media, especially for children with special needs, create a fun and interesting learning atmosphere. The understanding of numbers for children with special needs has made a lot of progress, children no longer forget numbers 1-10 and children feel happy because they use items that are liked by children. In children with special needs, the application of contextual learning methods assisted by number card media will motivate students to participate in active learning.